Labor Market Effects of Organizational Health Promotion - Gottfried, Péter (International Journal of Engineering and Management Sciences, 2021)
Nowadays, we can observe an increasing trend in the spread of non-communicable diseases. It is important to highlight the social factors that negatively affect health. Determinants includes income, education and the research-relevant working and living conditions. From a labor market perspective, unemployment and poor working conditions are a significant responsibility for the deterioration of mental and physical health. Health is also affected by employment conditions. Extended working hours have been shown to be harmful to health. Poor health has generates poorer work performance, a higher rate of sick leave, and higher health care costs. My primary goals in my research was to explore the labor market impacts of workplace health promotion and guidelines for corporate health promotion. Within health promotion, physical activity has played a prominent role. I’ve been used secondary data collection during my research. I have been performed a traditional literature analysis based on domestic and international studies. My results are suggest that the workplace health promotion has more positive labor market effects than increasing productivity and reducing absenteeism and health care costs. It is important to mention that health promotion could bring benefits to both employers and employees. Regarding corporate guidelines, there is no new approach directive other than the older literature sources. thus, it may be worthwhile to develop a new and different corporate process for effective workplace health promotion.